The Kola Saami Languages: Contemporary Sociolinguistic Situation - Ivanishcheva, Olga (Advances in Social Sciences Research Journal, 2014)
This paper shows that the Kildin Saami language belongs to the group of critically endangered languages, which means that the youngest speakers are grand-parents and older. Family ‘linguistic’ connections are completely lost, the language is transmitted only by ‘academics’ (language courses) and used partially. To preserve the Kildin Saami language only the following can be done: change the status of the language through the formation of a language policy and create new opportunities for language functioning. My research is based on the framework that contemporary sociolinguistic situation should be studied from the following perspectives: number of native speakers, the language environment, language revitalization, the state’s language policy, prestige of the language, existence of written forms of the language, and others.